Readiness of teachers on flexible learning: Basis for a capability-building program - Edelyn Alicar Cadorna; Erwin Frando Cadorna; Aldrin Salvador Jaramilla; Kriza Rosette Alicar Cadorna (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study focused on the faculty members’ readiness to use flexible learning at a state university in the Philippines. There were 547 faculty members from all levels completed an online survey questionnaire using the descriptive research method. The faculty members are ready regarding the availability of IT tools and internet connectivity. Still, they are not so much prepared as to their knowledge and competence on using flexible learning. The majority have wireless connections but are considered intermittent. Most of the faculty members use books as their teaching materials. Only very few have learning materials like modules, worktexts, manuals, and workbooks. Most of them are still oriented to face-to-face communication with students and are not familiar with the other equally responsive pedagogies requiring less data usage, or no data usage. Many faculty members have tried using online learning delivery modes, but they are still not confident using them. They have little knowledge about learning management systems and are moderately competent in using them. Based on the findings is the capability-building program which was already implemented and sustained.